THE USE OF ELECTRIC ENERGY FOR HOUSEHOLD NEEDS AT SUKAWATI DISTRICT, GIANYAR REGENCY: IN THE PERSPECTIVE OF CULTURAL STUDIES - Jondra, I Wayan; Agung, A. A. Gde; Wijaya Kusuma, I G. B.; Suastika, I Made (E-Journal of Cultural Studies; Vol. 5, No. 2 Juli 2011, 2012)
Sukawati District, Gianyar Regency is one of the tourist attractions anddestinations. Sukawati has Sukawati art market and Guwang market, art shops,craftsmen, wood carvers, painters, traditional and contemporary artists. They all completethe atmosphere at Sukawati. As a result, more and more people intend to build housesthere for which more and more electric energy is needed. This study was conducted toevaluate the use of electric energy at Sukawati District. The problems are formulated asfollows: how electric energy is used; how comodification takes place; how thegovernment and Perusahaan Listrik Negara, abbreviated to PLN (the Utility Company)dominates people and how the people resist the government’s hegemony, what are theeffects and meanings of the electric energy used at Sukawati District.Qualitative method supported by quantitative data, which characterize CulturalStudies, was adopted in this study. The data were taken from primary resources andsecondary resources. Qualitative method was eclectically employed for analyzing thedata supported by the theory of consumer behavior, the theory of comodification, thetheory of hegemony, the theory of knowledge and power and the theory ofdeconstruction. The results of the study were formally presented using tables, graphs andpictures and were informally narrated.The results of the study show that the increase in the number of population hasresulted in the increase in the number of traditional houses without/with slightmodification and modern houses. The rise in the number of houses has resulted in the risein electricity needed for illumination, mechanical purposes and so forth. The peopleliving at traditional houses use less and simpler electric utilities than those living atmodern houses. The electric utilities used are highly influenced by both internal andexternal factors. The advertisements of electric utilities also contribute to the use ofelectric utilities, meaning that electricity has touched what is required by the people atSukawati District. By referring to the 1945 Constitution, the PLN has dominated thedistribution of electricity. This has been used to comodify electric energy by changing itsstatus into a limited liability company, and to increase the basic rate of electricity (tarifdasar listrik, abbreviated to TDL) with its various scenarios socialized through massmedia. The government and the PLN dominate the community to accelerate their comodification practices. Such a dominance or hegemony is resisted by the traditionalpeople by strengthening their Balinese identity through the preservation of Balitraditional houses. Electricity has covered all the banjar/dusun (neighborhood under avillage) resulting in different effects such as giving up bathing in the public bathingplace, the extinction of informal communication among the people, renegotiation ofsacred values, change in orientation of the sekas (the traditional groups established forparticular purposes) from being orientated their activities to non economic motivationsinto economic ones. The different backgrounds of the people at Sukawati District havecaused the meaningfulness of the availability of electricity to vary.
Keywords: traditional houses, electricity and efficiency